Oscillatory Regulation of Hes1: Discrete Stochastic Delay Modelling and Simulation - Barrio, Manuel; Burrage, Kevin; Leier, André; Tian, Tianhai (PLoS computational biology, 2006)
Discrete stochastic simulations are a powerful tool for understanding the dynamics of chemical kinetics when there are small-to-moderate numbers of certain molecular species. In this paper we introduce delays into the stochastic simulation algorithm, thus mimicking delays associated with transcription and translation. We then show that this process may well explain more faithfully than continuous deterministic models the observed sustained oscillations in expression levels of hes1 mRNA and Hes1 protein.